Audit Mini Komunikasi dalam Event Business Bootcamp dan Pemberdayaan Perempuan di Trenggalek - Suryani, Emmy; Adawiyah, Sa’diyah El (LPPM Stikosa - AWS, 2025)
Trenggalek Regency organized the Perempuan Hebat Trenggalek Meroket event as part of a public relations initiative for women's empowerment, successfully attracting over 1,700 participants within six months. This research aims to evaluate the event’s effectiveness in empowering women, identify vulnerabilities and provide recommendations through qualitative analysis. This study employs a communication mini-audit to examine four aspects: management, organization, communication, and feedback. The management aspect is analyzed using Joe Goldblatt's event management theory. The researchers collected data through in-depth interviews and documentation. The findings indicate that the event effectively contributed to women's empowerment. Vulnerabilities were identified in the management aspect, particularly in the preparation phase and coordination between the Trenggalek Regency Government and village heads. Additionally, the evaluation process between the Event Organizer and the Trenggalek Regency Government had not been conducted thoroughly. In the communication aspect, vulnerabilities points were identified in the Trenggalek Regency Government's limited communication with village heads and the insufficient publicity of the event's impact